Penyelesaian Sengketa Hak Kepemilikan Tanah (Studi Pada Masyarakat Desa Pandan Sejahtera Dengan Pt. Indonusa Agromulia Kecamatan Geragai Kabupaten Tanjung Jabung Timur): Studi Pada Masyarakat Desa Pandan Sejahtera Dengan Pt. Indonusa Agromulia Kecamatan Geragai Kabupaten Tanjung Jabung Timur - Iping, Baso; Patmawanti, Besse (Jurnal Panorama Hukum, 2021)
This research aims to explore the land conflict between Pandan Sejahtera village societies and PT. Indonusa Agromulia Geragai District East Tanjung Jabung Regency and the obstacles faced in finishing. The method used in this research is qualitative method. The data consist of primary and secondary. Data collection procedures through observation, interview and documentation. The technique of data analysis is qualitative and presented in the descriptive. Based on the research concluded: first, the process of land conflict solution between Pandan Sejahtera village societies and PT. Indonusa Agromulia Geragai District East Tanjung Jabung Regency through out of court and by court. The step of conflict solution through out of court by facilitation and meditation, where the government of East Tanjung Jabung has role as facilitator and mediator. Even though, in this process can’t solute conflict that happen until follow the second way through court. The second way also can’t be followed by Pandan Sejahtera village societies because they never receive the state court of East Tanjung Jabung Regency. Moreover, Pandan Sejahtera village societies ask to the government of East Tanjung Jabung to facilitate and mediate the conflict solution. Second, the obstacles faced in the land conflict solution of Pandan Sejahtera village societies and PT. Indonusa Agromulia, namely: (a) the absence who follow conflict; (b) no good perception from each follow conflict; (c) the difference abilities and education between them; and (d) the regulation assumed make late the process of conflict solution, because part of government of East Tanjung Jabung as facilitator and mediator can’t be as the decision maker.